2012
DOI: 10.1155/2012/314056
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemic Renal Failure in Nonhematologic Solid Tumors: A Case Report and Review of the Literature

Abstract: Tumor lysis syndrome (TLS) is an oncologic emergency that is caused by massive tumor cell lysis. It is commonly associated with hematological cancers like leukemia and lymphoma and uncommonly with solid nonhematologic tumors as well. However, spontaneous tumor lysis syndrome (STLS) without any cytotoxic chemotherapy rarely occurs in solid tumors. We describe a case of STLS in a metastatic adenocarcinoma of unknown primary and review the literature of STLS in solid non-hematologic tumors to identify various ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Additionally, the preceding acute kidney injury in our patient may have contributed to the precipitation of STLS. While our case is not the first case of STLS by an undifferentiated adenocarcinoma of unknown origin, Saini et al [ 8 ] reported a mass that stained positive for CK7, CK20, mucicarmine, and villin, but negative for ER, mammaglobin, TTF-1, napsinA, CDX2, p63, calretinin and hepatocyte antigen that was suggestive of a non-colorectal gastrointestinal origin. This staining differs from our patient’s adenocarcinoma, and the group did not report serum tumor markers [ 8 ].…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Additionally, the preceding acute kidney injury in our patient may have contributed to the precipitation of STLS. While our case is not the first case of STLS by an undifferentiated adenocarcinoma of unknown origin, Saini et al [ 8 ] reported a mass that stained positive for CK7, CK20, mucicarmine, and villin, but negative for ER, mammaglobin, TTF-1, napsinA, CDX2, p63, calretinin and hepatocyte antigen that was suggestive of a non-colorectal gastrointestinal origin. This staining differs from our patient’s adenocarcinoma, and the group did not report serum tumor markers [ 8 ].…”
Section: Discussionmentioning
confidence: 52%
“…Though spontaneous tumor lysis syndrome is associated with hematologic malignancies, case reports in solid malignancies appear to show a common feature, namely a high tumor burden in the liver. Our patient shared this feature [7][8][9][10][11][12][13][14][15][16]. Additionally, the preceding acute kidney injury in our patient may have contributed to the precipitation of STLS.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Nephrotoxic agents like non-steroidal anti-inflammatory drugs, antibiotics, contrast, and drugs that interfere with uric acid excretion (thiazide diuretics, acetylsalicylic acid) should be avoided. 10…”
Section: Discussionmentioning
confidence: 99%